High-entropy double-phase sulfide as well as preparation method and application thereof

By introducing Cu and Al elements into polymetallic sulfides, a six-component high-entropy sulfide absorbing material with a biphasic structure is synthesized, the element separation problem is solved, the interface polarization effect is enhanced, and the efficient electromagnetic wave absorption performance is achieved.

CN119735245AActive Publication Date: 2025-04-01HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411900823.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing polymetallic sulfides have element separation problems when improving electromagnetic wave attenuation performance, making it difficult to achieve dielectric response and interface polarization attenuation synchronously, and high configuration entropy weakens the interface polarization effect.

Method used

By introducing Cu and Al metal elements, a six-component high-entropy sulfide absorbing material with a biphasic structure was synthesized by solubilizing heat and annealing methods. All metal elements were evenly distributed in the M9S8 and MS phases, forming a heterogeneous interface structure and abundant vacancy defects.

Benefits of technology

The coordinated improvement of conductivity loss, defect-induced polarization loss and interface loss is achieved, and the impedance matching and attenuation coefficient are optimized, thereby obtaining excellent electromagnetic wave absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735245A_ABST
    Figure CN119735245A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy double-phase sulfide and a preparation method and application thereof, and belongs to the field of electromagnetic wave absorbing materials. The invention aims to solve the problem of how to enhance the weak interface polarization effect of the high-entropy sulfide in electromagnetic attenuation. According to the invention, a solvothermal and annealing method is used, metal elements of Cu and Al are introduced into a multi-metal sulfide, a six-component high-entropy sulfide wave-absorbing material (6-HES) with a double-phase structure is synthesized, and all the metal elements are uniformly distributed in two phases of M9S8 and MS (M represents a metal element) with lattice defects. The high-entropy double-phase sulfide prepared by the method has a heterogeneous interface structure and abundant vacancy defects, so that the conductivity loss of the high-entropy double-phase sulfide can be improved, and the defect-induced polarization and interface loss can be enhanced. The invention excavates the potential of the polymetallic sulfide in the field of electromagnetic attenuation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electromagnetic wave absorbing materials, and specifically relates to a high-entropy two-phase sulfide and a preparation method and application thereof. Background Art

[0002] The booming development of the intelligent era, especially the 5G era or the future 6G era, has significantly promoted the widespread application of high-frequency intelligent electromagnetic devices represented by gigahertz (GHz) frequencies, but the resulting information leakage, electromagnetic pollution and other problems are becoming increasingly serious. Since the electronic structure, lattice defects and phase composition of polymetallic sulfides can improve the dielectric response by introducing metal elements, they have received widespread attention in alleviating electromagnetic problems.

[0003] According to the Hume-Rothery theory, metal elements with different ionic radii and electronegativity are introduced into polymetallic sulfides to create lattice defects in specific crystal phases (Small 2024, 2309773). Vacancy defects can serve as defect centers to enhance defect-induced polarization losses (Nano-Micro Lett. 2025, 17, 24.). However, improving dielectric loss only by introducing the enhanced polarization effect of sulfur vacancies is relatively simple, which hinders the further development potential of polymetallic sulfides in electromagnetic attenuation. It is worth emphasizing that application numbers 202311174922.X (publication (announcement) number: CN117039135A, publication (announcement) date: 20231110) and 202410638819.4 (publication (announcement) number: CN118600455A, publication (announcement) date: 20240906) disclose that high entropy sulfides exhibit the property of improving electrical conductivity. In addition, constructing a multiphase structure with a heterogeneous interface is another effective method to increase polarization loss, specifically, opposite charges tend to accumulate at the heterogeneous interface, thereby generating interface polarization to attenuate electromagnetic wave energy (Adv. Funct. Mater. 2022, 2204370). However, traditional polymetallic sulfides have the problem of element separation, and it is difficult to simultaneously implement the above modulation method to attenuate electromagnetic wave energy.

[0004] The high configurational entropy of high-entropy materials with application number 202410595991.6 (publication number CN118507749A, publication date: 20240816) can make a variety of metals evenly dispersed in a specific phase to avoid the separation of multiple elements. However, high configurational entropy generally promotes the formation of a single-phase structure rather than a multi-phase structure, which directly weakens or even eliminates the promoting effect of interfacial polarization in the attenuation of electromagnetic wave energy in high-entropy sulfides. In addition, the strong reactivity gives specific metal atoms a preferential chemical reaction advantage, thereby preferentially forming certain crystalline phases during the synthesis process (Adv. Sci. 2023, 2307649). Therefore, on the basis of improving conductivity loss and defect-induced polarization loss, how to enhance the weak interfacial polarization effect of high-entropy sulfides in electromagnetic attenuation is of great significance. Summary of the invention

[0005] In order to make up for the shortcomings of the existing preparation technology, the present invention provides a high entropy dual-phase sulfide absorbing material and a preparation method thereof. The present invention uses a high entropy strategy, solvent thermal and annealing methods to introduce Cu and Al metal elements into polymetallic sulfides, and synthesizes a six-component high entropy sulfide absorbing material (6-HES) with a dual-phase structure, in which all metal elements are uniformly distributed in M ​​with lattice defects. 9 S 8 The high entropy dual-phase sulfide prepared by the method of the present invention has a heterogeneous interface structure and rich vacancy defects, which can not only improve its conductivity loss, but also enhance the defect-induced polarization and interface loss. By simultaneously exerting the effects of the three loss mechanisms, 6-HES obtains optimized impedance matching and attenuation coefficient, thereby obtaining excellent electromagnetic wave absorption performance.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The object of the present invention is to provide a high entropy dual-phase sulfide, which includes six metal elements of iron, cobalt, nickel, chromium, copper and aluminum, and the atomic composition of each metal element accounts for 10%-30%. The high entropy dual-phase sulfide has M 9 S 8 Cubic structure and MS hexagonal structure.

[0008] It is further defined that the high entropy two-phase sulfide is particles with a particle size mainly concentrated in the range of 1 μm to 5 μm and a yolk-shell structure.

[0009] It is further defined that the mixing entropy of the high entropy two-phase sulfide is greater than or equal to 17.625 J / Mol / K.

[0010] The present invention also provides a method for preparing high entropy dual-phase sulfide, which is to use Fe(NO3 ) 3 9H 2 O (mass purity 99%), Co (NO 3 ) 2 6H 2 O (mass purity 99%), Ni (NO 3 ) 3 6H 2 O (mass purity 98%), Cr (NO 3 ) 2 9H 2 O (mass purity 98.5%), Cu(NO 3 ) 2 ·3H 2 O (mass purity 98.5%), Al (NO 3 ) 3 9H 2 O (mass purity is 99%) metal nitrate as raw material, the preparation method comprises the following steps:

[0011] Step 1, introducing glycerol into isopropanol, adding nitrate of metal element, stirring until uniformly mixed to obtain a uniform suspension, performing a solvothermal reaction on the obtained suspension, standing to cool, centrifugally washing with anhydrous ethanol until the upper liquid is clear, and vacuum drying to obtain a precursor;

[0012] Step 2: dissolving the precursor in anhydrous ethanol, adding thioacetamide, stirring until uniformly mixed to obtain a uniform suspension, subjecting the obtained suspension to a solvothermal reaction, centrifuging after cooling, washing the precipitate by centrifugation with anhydrous ethanol until the upper liquid is clear, vacuum drying, annealing under inert gas protection, and cooling to room temperature with the furnace to obtain a high entropy two-phase sulfide.

[0013] It is further defined that in step 1, 1 mL-10 mL of glycerol is introduced into 20 mL-80 mL of isopropanol, and the amount of each metal nitrate substance is 1 mmol-5 mmol.

[0014] It is further defined that the stirring rate in step 1 is 500r / min-1000r / min; and the stirring time is generally controlled at 30min-60min.

[0015] It is further defined that in step 1, the solvent thermal reaction is carried out at 120° C.-180° C. for 6 h-12 h; the solvent thermal reaction can be carried out in a stainless steel autoclave lined with Teflon.

[0016] It is further defined that in step one, the speed of the centrifuge is controlled at 8000r / min-12000r / min.

[0017] It is further defined that in step one, the vacuum drying in step one is carried out in a vacuum oven at 60°C-80°C for 8h-16h.

[0018] It is further defined that in step 2, 50 mg-100 mg of the precursor is dissolved in 30 mL-60 mL of anhydrous ethanol, and the amount of thioacetyl is 160 mg-190 mg.

[0019] It is further defined that the stirring rate in step 2 is 500r / min-1000r / min; and the stirring time is generally controlled at 30min-60min.

[0020] It is further defined that in step 2, the solvent thermal reaction is carried out at 150° C.-180° C. for 6 h-12 h; the solvent thermal reaction can be carried out in a stainless steel autoclave lined with Teflon.

[0021] It is further defined that in step 2, the annealing process is: heating at a rate of 2°C / min-7°C / min to 400°C-500°C, and annealing is carried out for 1h-3h. The inert gas is argon. The annealing is carried out in a tubular furnace. The dried precipitate is placed in an alumina corundum crucible and placed inside the tubular furnace. The gas in the tubular furnace is evacuated and filled with argon, and then the temperature is increased.

[0022] It is further defined that in step 2, the speed of the centrifuge is controlled at 8000r / min-12000r / min.

[0023] It is further defined that in step one, the vacuum drying in step two is carried out in a vacuum oven at 60° C.-80° C. for 8 h-16 h.

[0024] Any of the above high entropy dual-phase sulfides or high entropy dual-phase sulfides prepared by any of the above methods are used as electromagnetic wave absorbing materials.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention synthesizes a high entropy two-phase sulfide absorbing material with crystal defects, wherein the high entropy effect adjusts the electronic structure, resulting in an increase in conductivity and conductivity loss, an increase in crystal defect density leads to an enhancement in defect-induced polarization loss, and the interface polarization excited by the two-phase interface together improves the electromagnetic wave absorption performance.

[0027] The present invention precisely controls the synthesis of high-entropy sulfides with a dual-phase structure by selecting the metal elements Cu and Al, eliminates the weak interface polarization effect of high-entropy sulfides, and fully explores the potential of polymetallic sulfides in the field of electromagnetic attenuation.

[0028] The preparation process of the invention has simple operation, low equipment requirements and low cost.

[0029] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the X-ray diffraction (XRD) pattern of the five-element high entropy dual-phase sulfide in the comparative example of the present invention;

[0031] Figure 2 The scanning electron microscope image (SEM) and element distribution diagram (EDS) of the five-element high entropy dual-phase sulfide in the comparative example of the present invention;

[0032] Figure 3 This is a graph showing the electromagnetic wave absorption performance of the five-element high entropy two-phase sulfide in the comparative example of the present invention;

[0033] Figure 4 is the X-ray diffraction (XRD) pattern of the hexavalent high entropy dual-phase sulfide in Example 1 of the present invention;

[0034] Figure 5 The scanning electron microscope image (SEM) and element distribution map (EDS) of the hexavalent high entropy dual-phase sulfide in Example 1 of the present invention;

[0035] Figure 6 This is a graph showing the electromagnetic wave absorption performance of the hexavalent high entropy dual-phase sulfide in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0037] Example 1: The preparation method of the hexavalent high entropy dual-phase sulfide in this example is achieved by the following steps:

[0038] 1. Weigh 34 mL of isopropanol into a beaker, and introduce 6 mL of glycerol into the isopropanol.

[0039] 2. Take 0.5mmol of Fe(NO 3 ) 3 9H 2 O (mass purity 99%), Co (NO 3 ) 2 6H 2O (mass purity 99%), Ni (NO 3 ) 3 6H 2 O (mass purity 98%), Cr (NO 3 ) 2 9H 2 O (mass purity 98.5%), Cu(NO 3 ) 2 ·3H 2 O (mass purity 98.5%), Al (NO 3 ) 3 9H 2 O (mass purity 99%) metal nitrate is used as a raw material and dissolved in the mixed solution obtained in step 1. The solution is then stirred at a speed of 800 r / min for 30 min to obtain a uniformly mixed suspension.

[0040] 3. The obtained suspension was transferred to a 100 ml stainless steel autoclave lined with Teflon, and the solvent thermal reaction was carried out at 150°C for 10 hours. After cooling, the reaction product was taken out.

[0041] 4. The reaction product was centrifuged several times with anhydrous ethanol until the upper layer was clear, and the centrifuge speed range was 8000r / min. Then it was dried in a vacuum oven at 60°C for 8h, and the obtained powder was collected to obtain the precursor for synthesizing high entropy dual-phase sulfide.

[0042] 5. Dissolve 100 mg of the prepared metal precursor in 50 mL of anhydrous ethanol, then add 167 mg of thioacetamide to the mixed liquid, and stir for 30 minutes to obtain a uniform suspension.

[0043] 6. The above liquid was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene for solvothermal reaction, wherein the reaction temperature was 160° C. and the reaction time was 8 h.

[0044] 7. After cooling, pour the heated liquid into a centrifuge tube, wash the precipitate with anhydrous ethanol, and separate the solid and liquid by centrifuge (speed is 8000r / min), and wash it 3 times until the upper clear liquid is obtained. Place the centrifuged product in a vacuum drying oven at 60℃ and dry it for 8 hours, and then collect the resulting powder.

[0045] 8. Place the dried precipitate in an alumina corundum crucible and place it inside a tubular furnace. Drain the gas in the tubular furnace and fill it with argon. Anneal in a 500°C tubular furnace for 2 hours with a heating rate of 5°C / min. Cool to room temperature with the furnace, and finally take out the sample to obtain a high-entropy dual-phase sulfide.

[0046] Comparative Example: The preparation method of five-component high-entropy two-phase sulfide is carried out according to the following steps: 1. Weigh 50 mL of isopropanol and put it in a beaker, and introduce 10 mL of glycerol into the isopropanol.

[0047] 2. Take 2mmol of Fe(NO 3 ) 3 9H 2 O (mass purity 99%), Co (NO 3 ) 2 6H 2 O (mass purity 99%), Ni (NO 3 ) 3 6H 2 O (mass purity 98%), Cr (NO 3 ) 2 9H 2 O (mass purity 98.5%), Cu(NO 3 ) 2 ·3H 2 O (mass purity 98.5%) metal nitrate was used as a raw material and dissolved in the mixed solution. The solution was then stirred for 30 minutes to obtain a uniform suspension.

[0048] 3. The obtained suspension was transferred to a 100 ml stainless steel autoclave lined with Teflon, and the solvent thermal reaction was carried out at 150°C for 10 hours. After cooling, the reaction product was taken out.

[0049] 4. The reaction product was centrifuged several times with anhydrous ethanol until the upper layer was clear, and the centrifuge speed range was 10000r / min. Then it was dried in a vacuum oven at 60°C for 8h, and the obtained powder was collected to obtain the precursor for synthesizing high entropy dual-phase sulfide.

[0050] 5. Dissolve 100 mg of the prepared metal precursor in 50 mL of anhydrous ethanol, then add 188 mg of thioacetamide to the mixed liquid, and stir for 30 minutes to obtain a uniform suspension.

[0051] 6. The above liquid was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene for solvothermal reaction, wherein the reaction temperature was 160° C. and the reaction time was 8 h.

[0052] 7. After cooling, pour the heated liquid into a centrifuge tube, wash the precipitate with anhydrous ethanol, and separate the solid and liquid by centrifuge (speed is 10000r / min), and wash it 3 times until the upper clear liquid is obtained. Place the centrifuged product in a vacuum drying oven at 60℃ and dry it for 12h, and then collect the resulting powder.

[0053] 8. Place the dried precipitate in an alumina corundum crucible and place it inside a tubular furnace. Drain the gas in the tubular furnace and fill it with argon. Anneal in a 500°C tubular furnace for 2 hours with a heating rate of 5°C / min. Cool to room temperature with the furnace, and finally take out the sample to obtain a high-entropy dual-phase sulfide.

[0054] The XRD pattern of the five-component high entropy dual-phase sulfide prepared from five metals and sulfur is shown in Figure 1 As shown by Figure 1 It can be seen that the two phases of high entropy dual-phase sulfide are M 9 S 8 and MS, where M represents a metal element.

[0055] The SEM image of the five-component high-entropy dual-phase sulfide prepared from five metals and sulfur is shown in Figure 2. Figure 2 As shown by Figure 2 It can be seen that all metal elements are evenly distributed in the two phases, and no element separation occurs. Combined with the XRD results, this method successfully synthesizes M 9 S 8 High entropy sulfides with two physical phases: and MS.

[0056] Figure 3 The reflection loss characteristics of a five-component high entropy two-phase sulfide made of five metals and sulfur are shown in the figure. Figure 3 As shown by Figure 3 It can be seen that the reflection loss value of the five-component high-entropy two-phase sulfide is -26.7dB, and the effective absorption bandwidth is 4.08GHz, indicating that it has M 9 S 8 High entropy sulfides in the MS phase exhibit excellent electromagnetic wave absorption properties.

[0057] The XRD pattern of the six-component high entropy dual-phase sulfide prepared from six metals and sulfur is shown in Figure 4 As shown by Figure 4 It can be seen that the two phases of high entropy dual-phase sulfide are M 9 S 8 and MS, where M represents a metal element.

[0058] The SEM image of the six-component high-entropy dual-phase sulfide prepared from six metals and sulfur is shown in Figure 2. Figure 5 As shown by Figure 5 It can be seen that all metal elements are evenly distributed in the two phases, and no element separation occurs. Combined with the XRD results, this method successfully synthesizes M 9 S 8 High entropy sulfides with two physical phases: and MS.

[0059] The reflection loss characteristics of the six-component high entropy dual-phase sulfide prepared from six metals and sulfur are shown in the figure below. Figure 6 As shown by Figure 6 It can be seen that the reflection loss value of the six-component high entropy two-phase sulfide is -43.05dB, and the effective absorption bandwidth is 4.96GHz, indicating that it has M 9 S 8 High entropy sulfides in the MS phase exhibit excellent electromagnetic wave absorption properties.

[0060] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.

Claims

1. A high entropy dual-phase sulfide, characterized in that: It includes six metal elements: iron, cobalt, nickel, chromium, copper and aluminum. The atomic composition of each metal element accounts for 10%-30%, and it has M9S8 cubic structure and MS hexagonal structure.

2. The high entropy dual-phase sulfide according to claim 1, characterized in that: It is granular, with a particle size mainly concentrated in the range of 1μm-5μm, and has an egg yolk-shell structure.

3. The high entropy dual-phase sulfide according to claim 1, characterized in that: Its mixing entropy is greater than or equal to 17.625 J / Mol / K.

4. A method for preparing the high entropy dual-phase sulfide according to claim 1, 2 or 3, characterized in that: The following steps are involved: Step 1: introduce glycerol into isopropanol, add nitrate of metal element, stir until uniform, react with solvent heat, stand and cool, wash with anhydrous ethanol by centrifugation until the upper liquid is clear, and vacuum dry to obtain a precursor; Step 2: dissolve the precursor in anhydrous ethanol, add thioacetamide, stir until uniform, react with solvent heat, centrifuge after cooling, wash the precipitate by centrifugation with anhydrous ethanol until the upper liquid is clear, vacuum dry, anneal under inert gas protection, and cool to room temperature with the furnace to obtain a high entropy two-phase sulfide.

5. The method according to claim 4, characterized in that: In step 1, 1 mL to 10 mL of glycerol is introduced into 20 mL to 80 mL of isopropanol, and the amount of each metal nitrate substance is 1 mmol to 5 mmol.

6. The method according to claim 4, characterized in that: In step 1, the solvent thermal reaction is carried out at 120°C-180°C for 6h-12h.

7. The method according to claim 4, characterized in that: In step 2, 50 mg to 100 mg of the precursor is dissolved in 30 mL to 60 mL of anhydrous ethanol, and the amount of thioacetyl is 160 mg to 190 mg.

8. The method according to claim 4, characterized in that: In step 2, the solvent thermal reaction is carried out at 150°C-180°C for 6h-12h.

9. The method according to claim 4, characterized in that: In step 2, the annealing process is as follows: the temperature is raised to 400°C-500°C at a heating rate of 2°C / min-7°C / min, and the temperature is kept for annealing for 1h-3h, and the inert gas is argon.

10. The high entropy dual-phase sulfide according to any one of claims 1 to 3 or the high entropy dual-phase sulfide prepared by the method according to any one of claims 4 to 9 is used as an electromagnetic wave absorbing material.

Citation Information

Patent Citations

  • Novel wave-absorbing material and preparation method thereof

    CN101445716A

  • Preparation method and application of high-toughness diboride-carbide complex-phase high-entropy ceramic

    CN114262229A

  • Method for synthesizing cubic boron nitride by taking high-entropy alloy as catalyst

    CN117702273A

  • High-entropy sulfide and preparation method and application thereof

    CN118507715A

  • Lithium-sulfur battery positive electrode material and preparation method thereof, positive electrode and lithium-sulfur battery

    CN118588918A